2014
DOI: 10.1590/1809-4392201400383
|View full text |Cite
|
Sign up to set email alerts
|

Copper toxicity for Scinax ruber and Rhinella granulosa (Amphibia: Anura) of the Amazon: Potential of Biotic Ligand Model to predict toxicity in urban streams

Abstract: In the last years many populations of anurans have declined and extinctions have been recorded. They were related to environmental pollution, changes of land use and emerging diseases. The main objective of this study was to determine copper sensitivity of the anuran of the Amazon Rhinella granulosa and Scinax ruber tadpoles at stage 25 and Scinax ruber eggs exposed for 96 h to copper concentrations ranging from 15 µg Cu L -1 to 94 µg Cu L , respectivamente. O modelo do ligante biótico foi usado para prever os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These fish species developed a wide range of adaptations at all levels of the biological organization to thrive in these dynamic extreme environments (Val & Almeida-Val, 1995;Gonzalez et al, 1998;Wood et al, 1998;Barletta et al, 2010;Duarte et al, 2013;Kochhann et al, 2013;Val et al, 2015;Prado-Lima & Val, 2016). Similarly, these adaptations to local conditions have been described for microorganisms, fungi, plankton, algae, plants, insects, crustaceans, amphibians, and a multitude of aquatic invertebrates (Couceiro et al, 2011;Junk et al, 2011;Franco-de-Sá & Val, 2014;Hamada et al, 2014;Lopes et al, 2016a). However, will these adaptations and abilities allow these organisms to survive future environmental changes, which make their environments even more challenging?…”
mentioning
confidence: 95%
“…These fish species developed a wide range of adaptations at all levels of the biological organization to thrive in these dynamic extreme environments (Val & Almeida-Val, 1995;Gonzalez et al, 1998;Wood et al, 1998;Barletta et al, 2010;Duarte et al, 2013;Kochhann et al, 2013;Val et al, 2015;Prado-Lima & Val, 2016). Similarly, these adaptations to local conditions have been described for microorganisms, fungi, plankton, algae, plants, insects, crustaceans, amphibians, and a multitude of aquatic invertebrates (Couceiro et al, 2011;Junk et al, 2011;Franco-de-Sá & Val, 2014;Hamada et al, 2014;Lopes et al, 2016a). However, will these adaptations and abilities allow these organisms to survive future environmental changes, which make their environments even more challenging?…”
mentioning
confidence: 95%
“…Adult anurans have highly permeable skin [13], making them sensitive to various environmental stressors (including toxins of anthropogenic origin). The latest research has indicated that human industrial activity (e.g., mining, agriculture) is amongst the main reasons for the decline of amphibian anuran populations [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%